The Book of Mormon a biography - Gutjahr, Paul C. 1962- (Princeton [u.a.] Princeton Univ. Press, 2012)
Joseph's gold bible -- Holy writ or humbug? -- Multiplying prophets -- Great Basin saints and the book -- Missionary work and the book -- Scholars and the book -- Illustrating the book -- The book on screen and stage -- Appendix 1. Notable Book of Mormon editions in English -- Appendix 2. Book of Mormon translations
Joseph's gold bible -- Holy writ or humbug? -- Multiplying prophets -- Great Basin saints and the book -- Missionary work and the book -- Scholars and the book -- Illustrating the book -- The book on screen and stage -- Appendix 1. Notable Book of Mormon editions in English -- Appendix 2. Book of Mormon translations.
Includes bibliographical references and index
Archivierung prüfen
Keywords: Book of Mormon -- History; Book of Mormon -- Criticism, interpretation, etc; Book of Mormon; Book of Mormon -- History; Book of Mormon -- Criticism, interpretation, etc